Structural Model of Financial and Digital Literacy in Preventing Online Gambling among Students - Sitti Hasbiah; Nurhayani Nurhayani; Ilma Wulansari Hasdiansa; Andika Isma; Hajar Dewantara (PT Mattawang Mediatama Solution, 2026)
Financial and digital literacy are essential competencies for college students, enabling them to manage their finances efficiently and avoid engaging in online gambling. Lack of risk awareness and poor self-control can make college students more vulnerable to harmful financial habits. This study explores how financial and digital literacy influence college students' financial behavior, with Financial Stress Reduction (FSR) and Better Self-Control and Budgeting Behavior (BSCB) acting as mediators of Gambling Risk Awareness (AGR) and Gambling Access Resistance (RGA). This study employed a quantitative, cross-sectional approach, surveying 517 students from various academic levels, selected through random sampling. Information was collected through an online survey consisting of 35 questions with a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.0.3. The results indicate that financial and digital literacy have a substantial impact on FSR and BSCB, fully mediating the relationship between literacy and AGR/RGA. These findings highlight the need to combine literacy programs with methods to manage financial stress and encourage responsible budgeting. Educational institutions are urged to combine literacy initiatives with training in self-control, financial planning, and digital security awareness.